Preoperative Extracorporeal Membrane Oxygenation for Postinfarction Ventricular Septal Defect. Issue 1 (February 2019) - Ram, Eilon; Kogan, Alexander; Orlov, Boris; Raanani, Ehud; Sternik, Leonid
Abstract : The mortality rate after the development of ventricular septal defect (VSD) remains high despite progress in pharmaceutical therapy, invasive cardiology, and surgical techniques. Although early surgical repair of postinfarction VSD is associated with a high mortality rate, in hemodynamic unstable patients surgery cannot always be postponed and surgical repair may be required urgently. We present two cases of patients diagnosed with postinfarction VSD who were in cardiogenic shock with multiorgan failure despite optimal treatment. They were therefore connected to venoarterial extracorporeal membrane oxygenation as a bridge to reparative surgery.